Strategi Meningkatkan Keputusan Berlangganan Pada Situs Berita Online - Aziz, Muh. Abdul (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2023)
The purpose of this study was to examine the influence of website design, and service quality on trust in electronic purchasing decisions. By using these variables, the use of these variables is able to solve problems that arise in Business Insight customers. The formulation of this problem is how to improve purchasing decisions. The large sample of this study is 100 Business Insight customers. The analytical tool in this study uses SEM AMOS (Structural Equation Modelling). The results showed that website design, and quality of service to trust affect purchasing decisions. The influence of website design on trust is significant; quality of service to trust has a significant effect; website design has a significant influence on electronic purchasing decisions; the quality of electronic services has a significant effect on electronic purchasing decisions; The influence of e trust on e purchase decisions is significant.